Factors associated with discharge against medical advice from Emergency Department, Universiti Kebangsaan Malaysia Medical Centre - Ahmad Khaldun Ismail,; Mohamad Ali S,; Che’ Man Z, (Fakulti Perubatan, UKM, 2016)
Patients who self-discharge against medical advice (DAMA) are susceptible to life-threatening consequences. By understanding the factors associated with DAMA, healthcare centres can build strategies to assist patients to receive optimal medical care and prevent unfavourable outcome. The objective of this study was to determine the factors associated with DAMA from the Emergency Department (ED) of Universiti Kebangsaan Malaysia Medical Centre (UKMMC). This was a prospective unmatched case control study conducted over a 4-month period. For every DAMA episode, two patients who were admitted on the same day were randomly selected as control. Following patient consent, data was collected using a standardized questionnaire. Patients were contacted by the investigator for information regarding hospitalization within two weeks of DAMA. Ninety three patients were recruited; 31 DAMA patients and 62 admitted patients. Payment method was significantly associated with DAMA (OR 3.17 95% CI 1.29-7.98; p=0.01). The likelihood of self-paying patients to take DAMA was three times higher than those who had a guarantor letter from their employer or insurance provider. Other factors which influence DAMA were family obligations (OR 4.08 95% CI 1.09-15.26; p = 0.03) and work problems (OR 3.83 95% CI 1.13-12.94; p=0.03). A total of 19.4% of DAMA patients left following symptomatic pain relief. A total of 80.6% DAMA patients were admitted to hospital within two weeks of the DAMA episode. Payment method significantly influences DAMA. Payment planning, social welfare services, non-governmental organization funds and the introduction of a national health policy scheme may aid hospital payment, alleviate financial limitation of patients and reduce DAMA episodes.